2021
DOI: 10.2147/jpr.s325230
|View full text |Cite
|
Sign up to set email alerts
|

High-Frequency Impulse Therapy for Treatment of Chronic Back Pain: A Multicenter Randomized Controlled Pilot Study

Abstract: Purpose This study aims to examine high-frequency impulse therapy (HFIT) impact on pain and function among patients undergoing care for chronic low back pain (CLBP). Methods A pilot randomized-controlled trial of HFIT system versus sham was conducted across 5 orthopedic and pain center sites in California, USA. Thirty-six patients seeking clinical care for CLBP were randomized. Primary outcome was function measured by the Six Minute Walk Test (6MWT). Secondary outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…The Oura ring can accurately measure sleep time, sleep onset latency, time spent in deep and light sleep, and wake after sleep onset [ 53 ]. Digital health products also include non-invasive vagal nerve stimulators, such as Nurosym, or Hinge Health Enso, a wearable that delivers high-frequency impulse therapy for pain [ 54 ]. Table 1 provides examples of DTx and other digital health and wellness technologies that can improve health outcomes.…”
Section: Digital Health Technologies For Improving Healthcare Outcomesmentioning
confidence: 99%
“…The Oura ring can accurately measure sleep time, sleep onset latency, time spent in deep and light sleep, and wake after sleep onset [ 53 ]. Digital health products also include non-invasive vagal nerve stimulators, such as Nurosym, or Hinge Health Enso, a wearable that delivers high-frequency impulse therapy for pain [ 54 ]. Table 1 provides examples of DTx and other digital health and wellness technologies that can improve health outcomes.…”
Section: Digital Health Technologies For Improving Healthcare Outcomesmentioning
confidence: 99%
“…A feasibility randomized controlled trial (RCT) found that HFIT provided a significant improvement in pain and function in comparison to a sham device among patients with chronic low back pain after four weeks. 20 However, little is known about how HFIT performs against traditional TENS. As a result, this study aimed to examine whether HFIT provided improvement in pain and function in comparison to traditional TENS and usual care among participants of a digital chronic MSK program with knee and low back pain.…”
Section: Introductionmentioning
confidence: 99%